1998
DOI: 10.1016/s0928-8244(98)00073-x
|View full text |Cite
|
Sign up to set email alerts
|

XIX. A transphyletic anti-infectious control strategy based on the killer phenomenon

Abstract: A strategy for the prevention and control of candidiasis, pneumocystosis, and tuberculosis, based on the idiotypic network of the yeast killer effect has been envisaged. Anti-idiotypic antibodies representing the internal image of a candidacidal, pneumocysticidal, and mycobactericidal killer toxin from Pichia anomala and idiotypes of killer toxin-neutralizing monoclonal antibodies mimicking the specific cell wall receptor of sensitive microorganisms might provide a unique approach for engineering innovative an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2002
2002
2006
2006

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…The W. saturnus var. mrakii MUCL 41968 killer toxin is active against a wide range of infectious agents including C. albicans and P. carinii (3)(4)(5). Extensive studies reported that WmKT or WmKT-like antiidiotypic antibodies could represent new therapeutic molecules for the treatment of microbial infections (11,12,(20)(21)(22).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The W. saturnus var. mrakii MUCL 41968 killer toxin is active against a wide range of infectious agents including C. albicans and P. carinii (3)(4)(5). Extensive studies reported that WmKT or WmKT-like antiidiotypic antibodies could represent new therapeutic molecules for the treatment of microbial infections (11,12,(20)(21)(22).…”
Section: Discussionmentioning
confidence: 99%
“…The emergence of infectious agents resistant to conventional treatments has highlighted the need for novel antimicrobial agents. Among the new potential antimicrobial molecules, specific yeast mycocins (killer toxins) represent promising candidates because they display wide spectra of activity (3,4). Because of its particularly wide spectrum of activity, the killer toxin (WmKT) produced by Williopsis saturnus var.…”
Section: Introductionmentioning
confidence: 99%
“…Even though the mechanism of action of PaKT or functionally equivalent antiidiotypic antibodies is still to be completely defined, it seems to rely on their interaction with a carbohydrate transphyletic KTR mainly constituted by β‐glucans and particularly expressed on the neosynthesized cell wall of sensitive microorganisms that could include human pathogenic protozoa (Conti et al 1998b). …”
mentioning
confidence: 99%
“…However, after certain modifications or conversions (e.g. based on idiotypic mimicry of the toxin), they can be applied as therapeutic 3,4 or prophylactic agents 5 . Yeast‐producing toxins with anticryptococcal activity have been reported 6,7 .…”
Section: Introductionmentioning
confidence: 99%